Overtourism and Animal Abuse in Santorini - Riky Ramadani Prabowo (SEIKO : Journal of Management & Business, 2022)
Abstract This research aims to analyze and describe overtourism issue and the animal abuse related to this phenomenon in one of the most touristic islands in South Europe, Santorini. The research focuses on problems that happened before the covid-19 pandemic. This research methodology is qualitative, in which the information is gathered using literature research and empirical data. The data comes from literature studies and media with written sources related to this research and the questionnaire with open questions to the organizations that protested against the issue before the pandemic. The results show that Santorini shares some overtourism problems such as overcrowding, animal abuse, and energy overconsumption. These problems have provoked the local residents to do protest rallies to react to an unwanted situation they experience. Keywords: Overtourism; Animal Abuse, Santorini